Quality of meals transported in university restaurant (Research, Society and Development, 2021)
The mode of transported meals is characterized by production in a place different from where it will be distributed, in this sense, it incurs in more stages with risks of contamination. Thus, this study aimed to evaluate the hygienic-sanitary conditions and temperature in the production and distribution of transported meals. Then, a cross-sectional study was carried out, with a quantitative approach in a University Restaurant, and for this, the temperature of the meals was monitored during the packaging phases, on receipt at the distribution site and in the distribution period, as well as an evaluation of the hygienic-sanitary conditions of the transport vehicle and the distribution unit. The technique recommended by the Brazilian Association of Collective Meal Companies was used to measure the temperature and a checklist adapted for the study was applied. Thus, it was found that 100% of the preparations of the heated chain in the distribution had a temperature above 60°C, representing compliance with legislation, however, the same could not be observed in the refrigerated chain, as the preparations showed 100% inadequacy in the distribution of meals. Regarding the level of adequacy of the hygienic-sanitary conditions of the transport vehicle (79.70%) and of the distribution unit (83.4%), they presented adequate hygienic conditions. In general, the results demonstrate the adoption of good manufacturing practices and partial adequacy of control in the distribution process of transported meals. In order for the unit to offer cold chain preparations with greater sanitary safety, it is necessary to review the production process, as well as the preparation storage equipment.